Comportamento ingestivo de ovinos mestiços Santa Inês e Dorper confinados - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The objective of the present study was to examine the feeding behavior of feedlot Santa Inês and Dorper crossbred sheep. The study involved 14 ewes with an average age of seven months, consisting of seven Santa Ines crossbreds (± 51 kg) and seven Dorper crossbreds (± 55 kg) that were fed a diet based on corn silage and wheat bran concentrate. Feeding behavior was assessed by observing the animals to determine the feeding, rumination, and resting times; the time expended per feeding, rumination, and idle bouts; the number of ruminated cuds and chews per ruminated cud; and the time taken to ruminate each cud. A completely randomized experimental design was adopted. Neither of the two genetic groups influenced (P > 0.05) any of the observed feeding behavior variables. The daily time dedicated to feeding was 302.75 min; to rumination, 397.32 min; and to idleness, 739.11 min. Feeding patterns for the feedlot Santa Inês and Dorper crossbred sheep were similar, with longer feeding times observed in the morning and evening periods. These results may be related to diets and phenotypic characteristics of similar breeds. Therefore, feedlot Santa Inês and Dorper crossbred sheep do not exhibit changes in feeding behavior.
Keywords: Alimentação; Mastigação merícica; Ócio; Ruminação; CNPQ:: CIÊNCIAS AGRÁRIAS